Development of a website-based integrated welfare literacy model / Muhammad Shobaruddin - Shobaruddin, Muhammad; Yuniarto, Saiful Rahman; Hendrawan, Muhammad Rosyihan; Avicenna, Fitria (Faculty of Information Management, 2023)
The rapid progression of technology presents an opportunity to bolster literacy levels through digital means. This research delves into the creation of a website-based integrated welfare literacy model, targeting the education and teaching sectors. Collaborating with the Malang City Education and Culture Agency, the study's objective is to uplift teacher literacy, anticipating a ripple effect on student learning. Leveraging a design method grounded in a needs survey, the website's development follows a testing and dissemination approach. An explanatory qualitative methodology, aided by Focus Group Discussions, forms the backbone of data collection. Participants encompass teachers, students, parents, and librarians from secondary schools in Malang City, Indonesia. The accumulated data guides the formulation of a model, which subsequently informs the website design, piloted with a teacher cohort. Through this endeavor, the research illuminates the potential of web-based platforms in reshaping literacy landscapes, underlining the significance of digital interventions in contemporary education